Psychosocial interventions for war affected population - Iynkaran, K.; Somasundaram, D.; Velintina, S.; Rathakrishnan, S.; Vijayasangar, T. (University of Jaffna, 2018)
Individuals, families and communities in North and East Sri Lanka, so-called border areas as well as rest of Sri Lanka have undergone three decades of war trauma, multiple displacements, injury, detentions, torture, and loss of family, kin, friends, homes, employment and other valued resources causing mental health and psychosocial problems among the people. A Task Force on Psychosocial Well-being set up by the Office for National Unity and Reconciliation (ONUR) to address the mental health and psychosocial consequences of the conflict. Designed a methodology to implement a Training of Trainers (TOT) in psychosocial work. Government and Non-Governmental workers is being trained to train the Government, Non-government and village resources to address the Mental Health and Psychosocial Support (MHPSS) needs of people using individual, family and community level interventions. Literature survey used to find the best practices for psychosocial rehabilitation. For the needs and context of the situation, qualitative and quantitative methods with the accepted tools, participatory action research and feedbacks used. Most of the families have undergone war trauma, disturbed family dynamics due to the loss, disappearance and separation of family members. Many were under poverty line with unemployment and resettlement issues. Level of nutrition low in these areas. There were high prevalence of Post-Traumatic Stress Disorder (PTSD), Depression, Anxiety, Alcohol and Drug Dependence and Abuse. Social parameters showed loss of social capital, increased Suicide and Attempted Suicide rates; Gender Based Violence; Child Abuse; indebtedness; multiple partners and youth antisocial behavior. Interventions were carried out using evidence based best practices including psychological first aid in crisis, psychoeducation, counselling, ventilation through creative arts and drama. Traditional methods such as calming techniques, memorialization and healing rituals as well as promoting inherent strengths and resilience factors to rebuild communities through inter-sectoral collaborations for education, nutrition and livelihoods etc. Social interventions included awareness raising, core group training, children, youth, elders group, widows group, working with differently abled and re-establish social capital such as improving community networks, relationships, trust, organizations, human resources, leaderships and collective efficacy. Interventions which were more effective were used and in-effective discontinued. Benefits of interventions based on regular assessment showed improvement in mental health and psychosocial well-being as shown in the progress in various social parameters (psychiatric diagnosis, deliberate self-harm, alcoholism, trust and hope) among the War affected population in Northern Sri Lanka.
Keywords: Affected population; Intervention; MHPSS; Psychosocial; War